Epidemiology, Risk Factors, Diagnosis and Treatment of Mucormycosis (Black Fungus): A Review - Upadhayay, Pragati; Bansal, Keshav; Goyal, Ahsas (Current Pharmaceutical Biotechnology, 2023)
The COVID-19 pandemic has shown an adverse effect worldwide, but in India, it has been observed during the second wave that people who recovered from COVID-19 infection developed a secondary infection because it grows in tandem with COVID-19 treatment. Meanwhile, news of a new deadly fungus has surfaced known as Mucormycosis (Black fungus). Mucormycosis is a fungal infection that invades the blood vessels and is caused by Mucormycetes, a group of fungi. Due to the post-pandemic effect of COVID-19 many fungal and bacterial diseases have affected the population. The reason behind the frequent development of opportunistic infections like mucormycosis is the use of steroids, oxygen masks, and antibiotics throughout the treatment of critically and severely ill patients with COVID-19. Inhaling filamentous fungi from the natural environment and a lack of supportive care units can be a risk factor for mucormycosis. It is usually found in people who are immunocompromised. Mucormycosis is more common in people with HIV/AIDS, COVID-19, congenital bone marrow disease, viral diseases, malignancies, severe burns, and irregularly or untreated and treated diabetes. This review emphasizes triggers that may precipitate mucormycosis related to corticosteroids, recent epidemiology, and incidence of mucormycosis. The infection was diagnosed and identified using a variety of cutting-edge medical techniques, including clinical diagnosis, histopathology, and serology. Many treatment methods, such as antifungal medications and therapies, have also been successfully used. The mortality rate, however, remains high due to an aggressive surgical excision or debridement and lack of early diagnosis.
Keywords: fungal infection